Crustal structure of the Ethiopian Northwestern Plateau and central Afar from receiver function analysis - Kibret, Birhanu Abera; Ayele, Atalay; Keir, Derek (Frontiers in Earth Science, 2023)
In magma-rich continental rifts extension by magma intrusion is thought to accommodate much of the extension. We aim to constrain major melt reservoirs in the crust during magma-rich rifting by applying P-to-S receiver functions (RFs) using legacy teleseismic data having magnitudes Mb >6.0 and epicentral distances ranging from 30° to 90° and collected between the years 2000 and 2013 in 17 temporary broadband stations in Ethiopia and Eritrea. The majority of the NW Plateau crust shows fast Vs of ~4–4.7 km/s with localized slow Vs (3.2km/s) and high Vp/Vs (1.85–2.0) in the mid-crust (~10–25 km depth). The seismic velocity beneath the Afar crust is fairly homogeneous except beneath the current locus of strain at the magmatic segments, which have a relatively fast Vs (~4.5 km /s) at a shallow (~6–14 km) depth underlain by slower Vs (<3.2km/s) and high Vp/Vs (2.0) at lower crustal depths (~20–25 km). The Moho is sharp beneath most of the plateau stations and more gradational beneath Afar with estimated values of 36-44 km in the NW plateau and 26-30 km in Afar. The results point towards the presence of partial melt in localized places in the mid-crust beneath the NW plateau, and in the lower crust beneath the west of Afar, and particularly focused in the lower crust beneath the magmatic segments in Afar. The results suggest that the lower crust is an important melt reservoir for rift-related magmatic processes. The presence of melt in the NW plateau crust is more difficult to explain but is potentially linked to the broad extension of the plateau, or lateral migration of melt from the rift.